PENGARUH KONSENTRASI SUKROSA DAN SIRUP GLUKOSA TERHADAP SIFAT KIMIA DAN SENSORIS PERMEN KERAS BELIMBING WULUH (Averrhoa bilimbi. L) - Deisi L. Engka; Jenny Kandou; Teltje Koapaha (Universitas Sam Ratulangi, 2016)
ABSTRACTStarfruit (Averrhoa bilimbi) known as star fruit acids, this is due starfruit containsfolic acid. In the Minahasa region known as starfruit bottle, starfruit is one of the agriculturalproducts that have not received the attention and good handling. For that need to bedeveloped processing technology in the form of processed foods such as hard candies. Hardcandy is one of the non-crystalline candies that have a hard texture, shiny and translucentappearance. The purpose of research is to determine the concentration of sucrose and glucosesyrup right by analyzing the chemical components as well as measuring the level ofpreference panelists include taste, aroma, texture and color of hard candies starfruit. Thisstudy uses a completely randomized design (CRD) each consisting of three replications withA treatment (70% sucrose and 30% of glucose syrup); B (75% sucrose and 25% of glucosesyrup); C (80% sucrose and 20% of glucose syrup); and D (85% sucrose and 15% of glucosesyrup). The results showed that the hard candies starfruit with treatment A, B, C, and D meetthe requirements of SNI when viewed from the water content 0.40 - 1.03%, ash content of0.01 - 0.05%, reducing sugar 12.84 - 17.71% and total acids 1.06 - 1.20%. The greater theamount of concentration sucrose added will produce candy starfruit increasingly violent. Theconcentration of sucrose and glucose syrup is right for the manufacture of hard candy starfruitis concentration sucrose 85% and 15%. The results of organoleptic test sucrose concentrationof 80% and 20% glucose syrup is the preferred treatment panelists.Keywords: Starfruit, Sucrose, Glucose Syrup, Hard Candy.